Weathering rates and anthropogenic influences in a sedimentary basin, São Paulo State, Brazil - da Conceicao, F. T.; Bonotto, Daniel Marcos [UNESP] (Elsevier B.V., 2004)
The weathering rate of rocks and chemical dynamics of the Corumbatai River basin, São Paulo State, Brazil, were evaluated using major elements as natural tracers. This basin has serious environmental problems in terms of quality of surface and rainwater, which affect the determination of weathering rate. The Corumbatai River, downstream from Rio Claro City, receives several elements/compounds through anthropogenic activities, with only K, SO42- and alkalinity yielding positive flux values. The negative flux of some anions/cations can be attributed to atmospheric loading mainly related to anthropogenic inputs, providing K a value of 16.7 ton/km(-2)a(-1) for the material removed by weathering in the Corumbatai River basin. This is equivalent to 26 x 10(6) kg of rock being removed each year by the Corumbatai River. The instantaneous flux was found to be a function of discharge, with the majority of dry residue (dissolved load) being transported during the summer (wet) months. The removed material in Corumbatai River basin derives mainly from two sub-basins (Cabegas River and Passa Cinco River), where the sandstones weather more easily than siltstones and claystones in the basin. (C) 2003 Elsevier Ltd. All rights reserved.